Chagas disease: Performance analysis of immunodiagnostic tests anti-Trypanosoma cruzi in blood donors with inconclusive screening results - Márcia M Ferreira-Silva (Elsevier, 2021)
Background: The screening ofTrypanosoma cruzi-infected blood donors using two serological techniques frequently leads to conflicting results. This fact prompted us to evaluate the diagnostic performance of four “in-house” immunodiagnostic tests and two commercially available enzyme-linked immunosorbent assays (ELISAs). Material and Methods: One hundred and seventy-nine blood donors, whose screening for Chagas disease was doubtful, underwent three in-house ELISAs, one in-house immunoblotting test (TESA-blot), and two commercial ELISAs (bioMérieux and Wiener) in an attempt to define the presence or absence of infection. Simultaneously, 29 donors with previous positive results from three conventional serological tests and 30 donors with constant negative results were evaluated. Results: The ELISA-Wiener showed the highest rate in sensitivity (98.92%) and the ELISA-bioMérieux, the highest specificity (99.45%), followed by the TESA-blot, which showed superior performance, with lower false-negative (2.18%) and false-positive (1.12%) rates. In series, the combination composed of the TESA-blot and ELISA-bioMérieux showed slightly superior performance, with trifunctional protein deficiency (TFP) = 0.01%. Conclusion: Our study confirms the high sensitivity and specificity of commercial kits. To confirm the presence or absence of T. cruzi infection, the combination of TESA-blot and ELISA-bioMérieux may be suggested as the best alternative. Individually, the TESA-blot performed the closest to the gold standard; however, it is not commercially available.